Beberapa Isu Statistik Dalam Desain, Analisis Dan Interpretasi Penelitian Epidemiologi Lingkungan - Suhartono, Suhartono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2004)
ABSTRACT A primary objective of many environmental epidemiologic studies is to associate potentially adverse exposures received in the community (or workplace) with potential biologic effects. Such association are strengthened considerably if exposure-response relationshipcan be found.Identification and characterization of exposure-response relationship in the residential community setting are made difficult by the general absence of documented data on individuals at risk and their potential exposures. There are some limitations of epidemiological studies of communities exposed to environmenttal comtaminants i.e. populations living in the vicinity of point source of exposure are usually small; persons living in any given area are usually heterogeneous either with respect to characteristics that can influence many health outcomes indepedently of exposure; actual population exposures are generally poorly defined and for many chemicals little or nothing known about toxicological effects; many of the health endpoints of interest are either rare; publicity related to the episode under study may produce or accentuate reporting bias; and the conduct of community studies is made difficult by the presence of a highly charged atmosphere of anger and fear. There are some Â statistical aspects of community based investigations of health effects are i.e. exploratory vs. confirmatory study; determining sample size and statistical power; identifying and controlling systematic sources of error; assessing interaction; determining the level of the investigation; power with ecological studies; limitations of multivariate models, etc. Â Key word : Statistical Issues, Environmental Epidemiologic Studies.